Circulating Extracellular Mitochondria in Cardiometabolic Disease: Harnessing the Potential for Diagnosis, Prognosis, and Treatment - Michail Spanos; Priyanka Gokulnath; Olivia Rosina Whittaker; Christopher Azzam; Emeli Chatterjee; Aarush Singh; Dimitrios Varrias; Michail Kladas; Gururaja Vulugundam; Dimitrios Raptis; Hamza Sabir; Zainab Sabir; et al. (Physiologia)
Mitochondria are crucial for cellular functioning, serving as both an intracellular energy source and a signaling organelle. Recent evidence also highlights their existence outside of cells, where they participate in cell-to-cell communication. Cardiometabolic disease (CMD) has a complex pathogenesis closely associated with mitochondrial dysregulation, inflammation, and metabolic abnormalities. This review explores the roles of circulating extracellular mitochondria (CEMI) in CMD, detailing how their various forms, whether as intact structures or within vesicles, contribute to CMD pathogenesis. We classify different forms of CEMIs and discuss their potential as biomarkers and therapeutic agents in CMDs. We also describe mitochondrial transplantation as an emerging therapy for restoring cellular function in damaged tissues. Finally, to standardize CEMI assessment, we propose the Universal CEMI Assessment Protocol (UCAP), a framework aimed at enhancing comparability and reproducibility across studies.